A study on UiTM student's participation in sport and it's effect on the study habits, time management and academic achievement / Suhaili Masdar - Masdar, Suhaili (2003)
Sports provide a forum for the teaching of responsibility, conformity, and subordination, of self, shaping behaviors by encouraging efforts, social achievements as well as academics achievement. Personal discipline is also influenced by participation in sports. This study aims to determine the effect participation in sport and academic achievement among UiTM athletes. The study investigates whether participation in sport among UiTM athletes has an impact on their Cumulative Grade Point Average (CGPA) as well as their study habits and their time management. This study also tries to identify student's athlete's purposes for participating in sport. Forty students were chosen from three team sports. These are football; netball and hockey that involved 20 male and 20 female students. A convenient method of sampling was chosen for this study, as this sampling is suitable and representative of the purpose of the study. Data collected was analyzed using Statistical Package For Social Sciences (SPSS) for Windows Version 6.0 software. The data were analyzed and interpreted using frequencies and percentages. The results of the study indicated that a majority of the students* athlete has a consistent time management and obtained good result in their Cumulative Grade Point Average (CGPA). The data also indicated that majority of the students athlete concentrate or are involved in one game.